Investigating the role of dystrophin isoform deficiency in motor function in Duchenne muscular dystrophy. Issue 2 (26th January 2022) - Chesshyre, Mary; Ridout, Deborah; Hashimoto, Yasumasa; Ookubo, Yoko; Torelli, Silvia; Maresh, Kate; Ricotti, Valeria; Abbott, Lianne; Gupta, Vandana Ayyar; Main, Marion; Ferrari, Giulia; Kowala, Anna; et al.
Abstract: Background: Duchenne muscular dystrophy (DMD) is caused by DMD mutations leading to dystrophin loss. Full‐length Dp427 is the primary dystrophin isoform expressed in muscle and is also expressed in the central nervous system (CNS). Two shorter isoforms, Dp140 and Dp71, are highly expressed in the CNS. While a role for Dp140 and Dp71 on DMD CNS comorbidities is well known, relationships between mutations expected to disrupt Dp140 and Dp71 and motor outcomes are not. Methods: Functional outcome data from 387 DMD boys aged 4–15 years were subdivided by DMD mutation expected effects on dystrophin isoform expression; Group 1 (Dp427 absent, Dp140/Dp71 present, n = 201); Group 2 (Dp427/Dp140 absent, Dp71 present, n = 152); and Group 3 (Dp427/Dp140/Dp71 absent, n = 34). Relationships between isoform group and North Star ambulatory assessment (NSAA) scores, 10 m walk/run velocities and rise time velocities were explored using regression analysis. Western blot analysis was used to study Dp427, Dp140 and Dp71 production in myogenic cells (control and DMD human), control skeletal muscle, DMD skeletal muscle from the three isoform groups and cerebral cortex from mice (wild‐type and DMD models). Grip strength and rotarod running test were studied in wild‐type mice and DMD mouse models. DMD mouse models were mdx (Dp427 absent, Dp140/Dp71 present), mdx52 (Dp427/Dp140 absent, Dp71 present) and DMD‐null (lacking all isoforms). Results: In DMD boys, mean NSAA scores at 5 years of age were 6.1 points lower in Group 3 than Group 1 ( P < 0.01) and 4.9 points lower in Group 3 than Group 2 ( P = 0.05). Mean peak NSAA scores were 4.0 points lower in Group 3 than Group 1 ( P < 0.01) and 1.6 points lower in Group 2 than Group 1 ( P = 0.04). Mean four‐limb grip strength was 1.5 g/g lower in mdx52 than mdx mice ( P = 0.003) and 1.5 g/g lower in DMD‐null than mdx mice ( P = 0.002). Dp71 was produced in myogenic cells (control and DMD human) and skeletal muscle from humans in Groups 1 and 2 and mdx mice, but not skeletal muscle from human controls, myogenic cells and skeletal muscle from humans in Group 3 or skeletal muscle from wild‐type, mdx52 or DMD‐null mice. Conclusions: Our results highlight the importance of considering expected effects of DMD mutations on dystrophin isoform production when considering patterns of DMD motor impairment and the implications for clinical practice and clinical trials. Our results suggest a complex relationship between dystrophin isoforms expressed in the brain and DMD motor function.